Nafāʼisulmanan, fī ẕikr-i faz̤āʼil-i Sayyidnā Abī al-Ḥasan - Ḥaidar, Shāh Muḥammad ʻAlī (SAMP early 20th-century Indian books project, 1934)
On the life of ʻAlī ibn Abī Tālib, 600 (ca.)-661, caliph of Islam.